ANALYSIS OF THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS WITHOUT PUBLIC ACCOUNTABILITY (SAK ETAP) ON THE PRESENTATION OF GIRIREJO VILLAGE UNIT'S COOPERATIVE FINANCIAL STATEMENTS - Muhammad Rasyid (Transpublika Publisher, 2022)
The Indonesian Institute of Accountants (IAI) publishes Financial Accounting Standards for Entities Without Accountability so that entities that have not gone public can provide accurate financial reports (SAK ETAP). In reality, many cooperatives still do not use SAK ETAP in the preparation of their financial statements. The purpose of this research is to identify how the Girirejo Village Unit Cooperative's financial statements should be presented under the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This study uses a qualitative approach to conduct a comparative study. Methods of collecting data by interview. The method employed is a comparison of the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) with the presentation of Girirejo's Village Unit Cooperative financial statements. In essence, SAK ETAP has been adopted in Girirejo's Village Unit Cooperative financial accounts. The financial accounts of Girirejo Village Unit Cooperative demonstrate that the balance sheet, income statement, equity report, cash flow statement, and notes to financial statements have all been presented; nevertheless, several items such as inventories and investments, tax obligations, and tax expenses have not been recorded.